A bibliometric analysis of knowledge development in smart tourism research. (13th May 2019) - Johnson, Abbie-Gayle; Samakovlis, Ioanna
Abstract : Purpose: The purpose of this paper is to examine the production of smart tourism knowledge, thereby revealing the development of the concept through collaborative networks. Design/methodology/approach: A bibliometric analysis, which enables visual mapping and observation of the domain, was conducted using journal articles retrieved during the period of 2000 to 2018. Findings: The understanding of smart tourism is shaped and enhanced through collaborative network of researchers. As the domain develops, its reach expands across different networks as well as core themes. Research limitations/implications: Data for the study was generated from English-written journal articles that were produced from a database search of specific keywords associated with smart tourism. Practical implications: Findings can prove useful to academic researchers and industry practitioners to aid their understanding of smart tourism research development, identify the underlying context and aid in coherent development of the concept. Originality/value: The paper is one of the first articles to provide a greater understanding of smart tourism as a research topic by examining its evolution in an academic context through bibliometric analysis. Abstract : 论智慧旅游发展的文献计量学研究 抽象 研究目的: 本论文对智慧旅游相关知识进行审阅, 并通过协作网络对其概念发展进行梳理。 研究设计/方法/途径: 本论文采用Gephi文献计量分析方法, 对其相关领域的发展进行视觉化处理, 构建出发展图。研究样本为2000年至2018年发表的期刊文章, 通过在线搜索数据库获得。 研究结果: 通过研究者之间的协作网络, 本论文研究结果对智慧旅游的认识清晰形成并且更加深刻。自智慧旅游领域发展以来, 其发展扩展到不同网络以及多个核心主题。 研究理论限制/意义: 研究样本只局限于数据库中的英文期刊文章, 以及采用有限的智慧旅游的关键词搜索。 研究实践意义: 研究结果对学术学者和业界人士有着深刻效用, 以帮助他们对智慧旅游研究发展构筑清晰理解, 找到其研究背景以及概念发展的核心过程。